The Conspiracist Theory of Power - Mert Can Bayar; Scott Radnitz (Politics and Governance)
In recent years, conspiracy theories have surged in democratic politics, enabling illiberal parties, movements, and politicians to win the votes of constituents who are disillusioned with mainstream democratic politics. Yet scholars of democratic backsliding have not fully grappled with the implications of conspiracism as the basis for a governing ideology. In this article, we argue that challenges to liberal democracy can be better understood by analyzing conspiracism as a theory of power in its own right. Conspiracy theories are formulated to identify the ultimate source of power in society. They attribute the occurrence of major historical and political events to malevolent actors and their secret activities, and their ideas can be fleshed out into a political program. We offer a conceptualization of conspiracism as a theory of power and analyze it alongside liberal and populist theories of power. We examine four facets of political theory—who should govern, who threatens power, what governing entails, and the constraints on power—to identify divergences and unexpected affinities across these bodies of thought. We argue that conspiracism is not merely a critique of power, but an intellectual foundation for a political regime embodied in autocracy, oligarchy, or an alternate technocracy. This analysis informs our understanding of a serious yet under‐theorized threat to liberal democracy.